2015
DOI: 10.17221/68/2015-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of linear mixed effects model and generalized model of the tree height-diameter relationship

Abstract: Models of height curves generated using a linear mixed effects model and generalized model were compared. Both tested models were also compared with local models of height curves, which were fitted using a nonlinear regression. In the mixed model two versions of calibration were tested. The first calibration approach was based on measurement of heights only in trees of the mean diameter interval, while the second calibration approach was based on measurement of tree heights in three diameter intervals. General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Mathematical technique of a system of uniform diameter and height regional functions is the approach known as the generalized model. The mixed effects regression models are able to achieve the same results than the generalized model [10, 33]. In this study new developed mixed effects parameters height-diameter relationships demonstrated similar statistical indexes as in the nonlinear generalized height-diameter regression models presented by Petrauskas et al [34].…”
Section: Discussionsupporting
confidence: 60%
“…Mathematical technique of a system of uniform diameter and height regional functions is the approach known as the generalized model. The mixed effects regression models are able to achieve the same results than the generalized model [10, 33]. In this study new developed mixed effects parameters height-diameter relationships demonstrated similar statistical indexes as in the nonlinear generalized height-diameter regression models presented by Petrauskas et al [34].…”
Section: Discussionsupporting
confidence: 60%
“…The mathematical technique for a system of uniform diameter and height regional functions is the approach known as the generalised model. The mixed effects regression models are able to achieve the same results as the generalised model 34 .…”
Section: Resultsmentioning
confidence: 80%
“…Their data showed that the best model performance was obtained for fir with the coefficient of determination 0.94 -0.95 and RMSE 1.94 -1.97 m. Better results than those our are conditioned by long term data series and more or less even-aged stand structure. Recent studies suggest using general mixed effect height-diameter models rather than general ordinary least square models because of their higher prediction accuracy (Adamec 2015;Mehtätalo et al 2015;Sharma et al 2016). This could also improve modelling of heightdiameter relation in markedly uneven-aged forests.…”
Section: Height-diameter Modelsmentioning
confidence: 99%